Pengaruh Nilai Pelanggan terhadap Kepuasan Pelanggan pada CV. Ukhuwah Tasikmalaya - Kurniawan, Rudi; Rachman, Arief; Siti Nurhamidah, Lena (EKOBIMA, 2023)
This study aims to determine Customer Value, Customer Satisfaction, and the effect of Customer Value on Customer Satisfaction at CV. Ukhuwah Tasikmalaya. This research includes associative descriptive research with a quantitative approach. The sampling technique uses saturated sampling and the population of this study is CV.Ukhuwah customers. Ukhuwah as many as 32 people. The data analysis technique used in this research is validity test, reliability test, simple regression test, determination test, hypothesis test, and t (partial) test. Data analysis in this study used IBM SPSS Statistics 25.Based on the results of data processing and distribution of questionnaires, it is known that the t count is 5,030 with a sig t count of 000, the significance value is less than 0.05 so Customer Value has a significant effect on Customer Satisfaction in CV. Ukhuwah Tasikmalaya. The results of the research coefficient of determination is 47.47% while the remaining 52.53% is influenced by other variables not examined in this study.